High impact speeches how to create and deliver words that move minds - Heller, Richard (London Pearson education, 2003)
Sooner or later, we all find ourselves in front of an audience with nothing more to rely on than the power of our words. To lead today is to be a great persuader. We need the ability to mobilise ideas, appeal to values and inspire action. To find the right words, and the memorable words, to carry an audience and change things.In the business world it is no longer enough for executives to be good at making things or selling them or keeping costs down. They are also expected to explain things and persuade people to do things, and so crafting good speeches has become an essential business skill and a component of any successful career. A good speech is a good career move. More and more of us, in life and work then, can expect to find ourselves in front of an audience hoping to move hearts and minds. If you want to shape a collective vision, craft a compelling case or simply explain your plans with clarity and purpose, this book will help you write and deliver a memorable speech. There are many different skills involved in speaking well, but ultimately you need to know how to choose and organise words - you need to be able to write. High Impact Speeches will teach you how. It will also help you to develop a unique style and a unique copmand of your subject, with techniques that have worked for some of the greatest speakers in history. A good speech can inform, persuade, win a debate, make money or make news. It can advance your career and enhance your reputation. A bad one can only bore or make enemies. Whether the speech that you are writing is for you or for your boss, this book will teach you how to deliver a winning speech - from scratch. Expert speech-writer for business-leaders and leading politicians, Richard Heller will show you how to: * Accept the right speaking opportunities (and reject the wrong ones) * Identify your desired result * Research your audience * Structure and plan your speech * Create an attention-grabbing beginning and a rousing finish * Make it rhythmic and colourful * Add changes of mood and pace * Deploy killer logic, winning arguments and powerful persuasion * Edit and refine the sharpest draft and rehearse for perfection * Carry your audience to their destination of agreeing with you "Essential reading for anyone who has to prepare and deliver a speech." - Baroness Boothroyd "No one is better suited to write a primer of speechmaking than Richard Heller. One of the few modern journalists with a real talent for language ...he has set out what to say and how to say it." Tribune
Includes index
Keywords: Speeches